Kegagalan Imitasi Strategi Global: Kasus Gerakan Occupy Jakarta - Mahayasa, Dias Pabyantara Swandita (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2015)
Occupy Wallstreet movement in the United States of America brought an awareness about economic imbalances of the world. As real indicator, they are many movements in some countries imitating Occupy Wallstreet movement. In Indonesia, such movement situated in Jakarta whose slogan Occupy Jakarta. This article analyzes the failure of Occupy Jakarta as the imitation of Occupy Wallstreet movement. The main argument proposed that visibility strategy used by Occupy Wallstreed was applicated without considering local reality in Jakarta. Using CAGE analysis from Ghemawat, this article found that the failure of Occupy Jakarta due to its failure in identifying the main problem in Indonesia, which are agrarian conflict and corruption. The main focus of Occupy Jakarta was against the share holder that did not get public attention so that this movement turn into its failure.